SUMOylation of the Farnesoid X Receptor (FXR) Regulates the Expression of FXR Target Genes - Balasubramaniyan, Natarajan; Luo, Yuhuan; Sun, An-Qiang; Suchy, Frederick J. (The Journal of biological chemistry, 2013)
The farnesoid X receptor (FXR) belongs to a family of ligand-activated transcription factors that regulate many aspects of metabolism including bile acid homeostasis. Here we show that FXR is covalently modified by the small ubiquitin-like modifier (Sumo1), an important regulator of cell signaling and transcription. Well conserved consensus sites at lysine 122 and 275 in the AF-1 and ligand binding domains, respectively, of FXR were subject to SUMOylation in vitro and in vivo. Chromatin immunoprecipitation (ChIP) analysis showed that Sumo1 was recruited to the bile salt export pump (BSEP), the small heterodimer partner (SHP), and the OSTα-OSTβ organic solute transporter loci in a ligand-dependent fashion. Sequential chromatin immunoprecipitation (ChIP-ReChIP) verified the concurrent binding of FXR and Sumo1 to the BSEP and SHP promoters. Overexpression of Sumo1 markedly decreased binding and/or recruitment of FXR to the BSEP and SHP promoters on ChIP-ReChIP. SUMOylation did not have an apparent effect on nuclear localization of FXR. Expression of Sumo1 markedly inhibited the ligand-dependent, transactivation of BSEP and SHP promoters by FXR/retinoid X receptor α (RXRα) in HepG2 cells. In contrast, mutations that abolished SUMOylation of FXR or siRNA knockdown of Sumo1 expression augmented the transactivation of BSEP and SHP promoters by FXR. Pathways for SUMOylation were significantly altered during obstructive cholestasis with differential Sumo1 recruitment to the promoters of FXR target genes. In conclusion, FXR is subject to SUMOylation that regulates its capacity to transactivate its target genes in normal liver and during obstructive cholestasis. Background: Small ubiquitin-like modifiers (SUMO) are covalently conjugated to other proteins including nuclear receptors leading to modification of various cellular processes. Results: Ligand-dependent SUMOylation of farnesoid X receptor (FXR) negatively regulates the expression of its target genes. Conclusion: SUMO modification attenuates the capacity of FXR to function as a transcriptional activator. Significance: Defining post-translation modification of FXR by SUMO is important to understanding how this nuclear receptor functions in health and disease.